Transverse seismic failure mechanism and ductility of reinforced concrete pylon for long span cable-stayed bridges: Model test and numerical analysis. (15th June 2019) - Wang, Xiaowei; Fang, Jiaxin; Zhou, Lianxu; Ye, Aijun
Highlights: A quasi-static pushover test on RC pylon of cable-stayed bridges is first reported; A simplified and efficient two-node lateral load-pattern for loading scheme is proposed; A refined numerical model of the RC pylon is built and validated by the test; Transverse failure mechanism and ductility of the RC pylon are summarized. Abstract: Although often designed to behave elastically, seismic damage to reinforced concrete (RC) pylons of cable-stayed bridges have been witnessed in history such as the 1999 Chi-chi earthquake. This paper aims to assess the transverse seismic failure mechanism and ductile properties of typical inverted Y-shape RC pylons for long span cable-stayed bridges using quasi-static model tests and numerical analyses. To facilitate the limited laboratorial loading system, a simplified displacement-controlled two-node load-pattern, one at the bifurcation-node and the other at the crossbeam, is first proposed using numerical analyses. It is found the ratio of displacements at the two loading nodes is correlated generally well with the ground motion parameter, bracketed duration. A displacement ratio of 5.0 is then adopted in the test. Test results indicate a flexural damage mode with considerable ductility: plastic hinges were detected first at bottom of the upper column (i.e., above the crossbeam), then at bottom and top of the lower column, successively; multi-level displacement ductility factors are proposed to associate with numbers of plastic hinges formed in the pylon. Moreover, an experimentally validated numerical model is adopted to study the impact of loading displacement ratios on the failure mechanism and ductility. It is found that the loading displacement ratios may significantly affect them. Smaller displacement ratios tend to transfer the location of first plastic hinge from the bottom of the upper column to that of the lower column.